2008
DOI: 10.1097/mpg.0b013e31817e0f2c
|View full text |Cite
|
Sign up to set email alerts
|

Altered Eicosanoid Metabolism in the Cystic Fibrosis Mouse Small Intestine

Abstract: There are changes in eicosanoid metabolic gene expression that are accompanied by significant changes in specific eicosanoid levels. These changes are expected to play important roles in the pathophysiology of CF in the intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…It has been shown that cytosolic PLA 2 is increased in lungs of CF mice and that challenge with lipopolysaccharide or arachidonic acid increases Muc5AC, whereas PLA 2 inhibition blocks this effect (15). At least two PLA 2 genes have increased expression in the adult CF mouse small intestine [(16) and the current study], which is accompanied by excessive mucus accumulation.…”
Section: Introductionmentioning
confidence: 86%
“…It has been shown that cytosolic PLA 2 is increased in lungs of CF mice and that challenge with lipopolysaccharide or arachidonic acid increases Muc5AC, whereas PLA 2 inhibition blocks this effect (15). At least two PLA 2 genes have increased expression in the adult CF mouse small intestine [(16) and the current study], which is accompanied by excessive mucus accumulation.…”
Section: Introductionmentioning
confidence: 86%
“…AA is a precursor of bioactive oxygenated metabolites known as eicosanoids, which include prostaglandins and leukotrienes. Production of these metabolites is known to be increased in CF, and several studies have drawn a connection between eicosanoid alterations and disease pathogenesis (54)(55)(56)(57)(58)(59). It is plausible that the observed benefi t of n-3 fatty acid therapy in the CF mouse model ( 6 ) and in a small subset of human trials ( 29,30 ) is due to its ability to normalize AA levels and, consequently, reduce excessive production of eicosanoids.…”
Section: Discussionmentioning
confidence: 99%
“…EFA deficiency in itself can cause fat malabsorption by affecting the absorption capacity of the intestine [74]. Apart from reduced LA and DHA levels, increased levels of AA in the CF intestine could also (indirectly) affect fat absorption, by contributing to intestinal inflammation, mucus secretion and intestinal smooth muscle relaxation [79]. It has been shown that EFA deficiency affects both the intra-luminal and intra-cellular process of fat absorption, as exemplified in (non-CF) animal models [69].…”
Section: Relation With Cfpfmmentioning
confidence: 99%